The Leader Vitality Scale: Development, Psychometric Assessment, and Validation - Shapiro, Jamie; Donaldson, Stewart I. (Frontiers in Psychology, 2022)
One of the most important units of analysis for positive organizational psychology research is leaders and future leaders in the workplace. Leaders often have a large responsibility for and influence on the well-being and performance of their followers. They also face the unique challenge of serving their followers and the organization while needing to maintain their own vitality and well-being. Vitality can provide a foundation of energy resources to a leader to serve at their full capacity. This study develops and empirically examines a new three factor scale to measure leader vitality which includes physical, psychological, and emotional components. In study 1, a total of 175 participants (including n = 128 leaders) completed the Leader Vitality Scale (LVS) and other positive psychology related measures. Exploratory factor analysis and then confirmatory factor analysis showed that the LVS is hierarchical with three distinct factors, with overall vitality as the higher-order factor. Correlational tests with two established vitality scales for general use showed that the LVS is positively related to existing scales, demonstrating convergent validity. In study 2, data was gathered from 92 top level leaders in the C-Suite (n = 25), vice presidents (n = 23), directors (n = 21), and managers (n = 23) of organizations across the United States. Results showed that LVS scores significantly correlated with life satisfaction, positive emotions, positive functioning at work, and psychological capital. Overall, these findings suggest that the LVS is a valid measure for assessing leader vitality, and can used in future studies of well-being and positive functioning at work.